Antitumor effect of infrared whole-body hyperthermia with curcumin in breast cancer - Saim, Hanim (Springer Science and Business Media B.V., 2022)
Infrared Hyperthermia therapy (IHT) is a non-contacting method to elevate body temperature and treat malignant lesions such as breast cancer. Breast cancer is one of the major cancer types among females and over the years, its prevalence is increasing. Current treatments of breast cancer are surgery, radiotherapy, chemotherapy and thermotherapy via the use of IHT or combination of these. IHT is most commonly combined with chemotherapy as its effect as a stand alone treatment platform is short lasting. However, chemotherapy induced toxicity to patients. Curcumin has traditionally been used as a food additive or as a remedy in traditional medicine for its anticancer and non-toxic effects. Thus, this research proposed the combination of curcumin and IHT as an alternative to chemotherapy in breast cancer treatment. Mice were inoculated with EMT6 breast cancer cells and assigned to 4 treatment groups: (i) untreated (control), (ii) orally curcumin (CUR), (iii) whole-body hyperthermia (FRWBH), (iv) orally curcumin with whole-body hyperthermia (FRWBH+CUR). Results showed that tumor growth inhibition and body weight gain in the combination treatment group (FRWBH+CUR) are significantly different compared to control. The group also had the longest median survival time (42 days) with no mortality observed during the experiment. This result indicates that the combination treatment is well tolerated by the mice and has negligible levels of toxicity. However, frequent complications of cancer such as anaemia and thrombocytopenia are still observed in the combination treatment group. Platelet to Lymphocyte Ratio (PLR) and Neutrophils to Lymphocytes Ratio (NLR) results indicate that the combination treatment (FRWBH+CUR) has better prognosis outcome than single treatment and may become a potential alternative antitumor treatment of breast cancer.